Hippocampal volume and volume asymmetry prospectively predict PTSD symptom emergence among Iraq-deployed soldiers. Issue 5 (22nd April 2023) - Cobb, Adam R.; Rubin, Mikael; Stote, Deborah L.; Baldwin, Brian C.; Lee, Han-Joo; Hariri, Ahmad R.; Telch, Michael J.
Abstract: Background: Evidence suggests a link between smaller hippocampal volume (HV) and post-traumatic stress disorder (PTSD). However, there has been little prospective research testing this question directly and it remains unclear whether smaller HV confers risk or is a consequence of traumatization and PTSD. Methods: U.S. soldiers ( N = 107) completed a battery of clinical assessments, including structural magnetic resonance imaging pre-deployment. Once deployed they completed monthly assessments of traumatic-stressors and symptoms. We hypothesized that smaller HV would potentiate the effects of traumatic stressors on PTSD symptoms in theater. Analyses evaluated whether total HV, lateral (right v. left) HV, or HV asymmetry (right – left) moderated the effects of stressor-exposure during deployment on PTSD symptoms. Results: Findings revealed no interaction between total HV and average monthly traumatic-stressors on PTSD symptoms b = −0.028, p = 0.681 [95% confidence interval (CI) −0.167 to 0.100]. However, in the context of greater exposure to average monthly traumatic stressors, greater right HV was associated with fewer PTSD symptoms b = −0.467, p = 0.023 (95% CI −0.786 to −0.013), whereas greater left HV was unexpectedly associated with greater PTSD symptoms b = 0.435, p = 0.024 (95% CI 0.028–0.715). Conclusions: Our findings highlight the importance of considering the complex role of HV, in particular HV asymmetry, in predicting the emergence of PTSD symptoms in response to war-zone trauma.